"Ciężarówka" czy "kobieta w stanie błogosławionym"? Prezentacja współczesnych sposobów postrzegania ciał kobiet spodziewających się potomstwa = "Bun in the oven" or "expectant mother"? Presentation of contemporary perceptions of pregnant women`s bodies - Hajda, Agata (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper presents the reflections on the metamorphosis in the perception of pregnant women`s physicality. It focuses on the moral sphere and the sources of the article relate primarily to the area of contemporary Poland (the examples are chosen at random due to the size of the article).
Keywords: kobieta w ciąży; ciało ludzkie; socjologia ciała